Antibacterial activity of phenyl isothiocyanate on Escherichia coli and Staphylococcus aureus - Abreu, Ana C. (2013)
The present study has been aimed to assess the antibacterial effects of the glucosinolate hydrolysis product phenyl isothiocyanate (PITC) against Escherichia coli and Staphylococcus aureus. Aspects on the antibacterial mode of action of PITC have also been characterized, such as the changes on surface physicochemical characteristics and membrane damage. The minimum inhibitory concentration of PITC was 1000 µg/mL, for both bacteria. The antimicrobial potential of PITC was compared with selected antibiotics (ciprofloxacin, erythromycin, streptomycin, tetracycline and spectinomycin),that reported a moderate effect. The combination of PITC with ciprofloxacin and erythromycin against S.aureus exhibited a good antimicrobial efficacy, due to an additive effect (the diameter of inhibition zones increased from 30 to 40 mm for ciprofloxacin and almost the double for erythromycin). The other combinations reported unsatisfactory results against both bacteria. The study of the physiological changes induced by PITC action demonstrated the interaction between the electrophilic compound and the bacterial cells at several points that causes changes in membrane properties (decreases negative surface charge, increases surface hydrophilicity and electron donor characteristics). PITC was also found to disturb membrane function, as manifested by phenomena such as cellular disruption and loss of membrane integrity, triggering cell death.